2020
DOI: 10.1186/s12906-019-2809-9
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal plants sold for treatment of bacterial and parasitic diseases in humans in Maputo city markets, Mozambique

Abstract: Background: In Mozambique, bacterial and parasitic diseases contribute to a high burden of mortality and morbidity. These infectious diseases are treated with antibiotics, antihelmintic or antiparasitic drugs. However, misuse of these has been affecting the potential to treat ailments. It has been reported that many people from Maputo city and province apart from the existing contemporary medicine, still use medicinal plants for treatment of diseases due to traditional heritage and beliefs. It is, therefore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…Hypoxis hemerocallidea is mentioned as one of the species used for the treatment of tuberculosis in Limpopo Province of South Africa [52]. The species was one of the most cited medicinal plants in the medicinal markets [53], used for treatment of malaria and venereal diseases in Mozambique [26,54]. Different Hypoxis spp.…”
Section: Uses and Chemical Composition Of Hypoxis Hemerocallideamentioning
confidence: 99%
“…Hypoxis hemerocallidea is mentioned as one of the species used for the treatment of tuberculosis in Limpopo Province of South Africa [52]. The species was one of the most cited medicinal plants in the medicinal markets [53], used for treatment of malaria and venereal diseases in Mozambique [26,54]. Different Hypoxis spp.…”
Section: Uses and Chemical Composition Of Hypoxis Hemerocallideamentioning
confidence: 99%
“…In other words, fruits are generally less demanded than bark but indigenous people hold relatively more knowledge on its uses compared to bark. Barbosa et al [18] suggested roots as the most used part when noticing that it was the most often sold part. Our results con rm the fact that the most sold part does not automatically mean the relatively more important in terms of uses.…”
Section: Diversity Of Illnesses Disorders Treated and Rituals Accordmentioning
confidence: 99%
“…Even with the intervention of antibiotics and antiparasitic drugs, the potential for treating some diseases has decreased due to the indiscriminate use of these drugs. As a result, the population has looked to medicinal plants for an alternative source for the treatment of diseases (SHARIFIFAR et al, 2016, BARBOSA et al, 2020.…”
Section: Artigo Introductionmentioning
confidence: 99%
“…R. & A. Fer. (Anacardiaceae), is marketed and traditionally used in Mozambique for the treatment of dysentery, inflammation of the chest, respiratory infections, low back pain, cough, chest pain, fever, diarrhea, and wounds (BANDEIRA;GASPAR;PAGULA, 2001, GRACE et al, 2003DE WET;VAN VUUREN, 2011, YORK;DE WET, 2012, WÜRGER;, SHARIFIFAR et al, 2016, BARBOSA et al, 2020. The potential against microorganisms that cause respiratory infections (YORK; VAN VUUREN; DE WET, 2012) and the presence of phenolic compounds (WÜRGER; MCGAW; ELOFF, 2014) in the leaves of O. obovata have already been reported.…”
Section: Artigo Introductionmentioning
confidence: 99%
See 1 more Smart Citation